2016
DOI: 10.1016/j.ensci.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic drugs in development pipeline: A recent update

Abstract: Epilepsy is the most common neurological disorder which significantly affects the quality of life and poses a health as well as economic burden on society. Epilepsy affects approximately 70 million people in the world. The present article reviews the scientific rationale, brief pathophysiology of epilepsy and newer antiepileptic drugs which are presently under clinical development. We have searched the investigational drugs using the key words ‘antiepileptic drugs,’ ‘epilepsy,’ ‘Phase I,’ ‘Phase II’ and ‘Phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…This demonstrates a continued need for developing new formulations with the aim of creating new concepts and original ideas to effectively prevent epilepsy or its progression. Recent ongoing clinical trials of epilepsy can be found in an interesting review published by Kaur et al, in which the current developmental status of new drugs for treatment of epilepsy and a brief description about antiepileptic drugs that are targeting different mechanisms were reported [31]. IN delivery of drugs on antiepileptic treatment or innovative formulations could overcome some of these drawbacks.…”
Section: Diagnosis and Antiepileptic Drug Treatment Of Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrates a continued need for developing new formulations with the aim of creating new concepts and original ideas to effectively prevent epilepsy or its progression. Recent ongoing clinical trials of epilepsy can be found in an interesting review published by Kaur et al, in which the current developmental status of new drugs for treatment of epilepsy and a brief description about antiepileptic drugs that are targeting different mechanisms were reported [31]. IN delivery of drugs on antiepileptic treatment or innovative formulations could overcome some of these drawbacks.…”
Section: Diagnosis and Antiepileptic Drug Treatment Of Epilepsymentioning
confidence: 99%
“…Instead, in the United States, the FDA has only approved one rectal AED formulation, Diastat ® , for home use [32]. As mentioned, there are a number of novel antiepileptic compounds that are under various stages of drug development and their current developmental status for treatment of epilepsy can be found in Kaur’s study [31]. These new drugs under clinical study are expected to provide better treatment options for epilepsy in terms of improved pharmacokinetics, safety, and efficacy.…”
Section: Antiepileptic Drugs: Limits During Treatmentmentioning
confidence: 99%
“…Thus while PARP was discovered as the main contributor to necrotic cell death and the first PARP inhibitor started a trial in ST-Elevation Myocardial Infarction (STEMI) [35], PARP inhibitors reached the market later as cancer drugs: currently olaparib, rucaparib and niraparib are approved for ovarian cancer [36,37]. Similarly, caspase inhibitors were initially suggested to play a role as potential drugs in a wide array of diseases including acquired immune deficiency syndrome (AIDS), ischemic diseases (myocardial infarction, stroke), neurodegenerative diseases, myelodysplatic syndrome and toxic liver injury [38], but clinical trials were only started in epilepsy, hepatitis C virus (HCV) infection and non-alcoholic steatohepatosis (NASH) and none of the caspase inhibitors have reached FDA approval [39][40][41].…”
Section: Planning a Phenotypic Screenmentioning
confidence: 99%
“…In phase I clinical trials to healthy subjects, carisbamate has shown linear pharmacokinetics at doses of 100 to 1,500 mg, high oral bioavailability (F) of > 95% and a low oral clearance (CL/F) of 3.4–4.2 L/h, equaling < 5% of liver blood flow [ 1 2 7 ]. The drug also has shown efficacy and tolerability in a phase II clinical trial for epilepsy patients, and three phase III clinical trials have been completed for treatment in partial seizures [ 8 9 10 ]. Among them, only one phase III clinical trial (randomized double-blind) study showed significant efficacy results in adults with refractory partial seizures receiving a dose of 400 mg/day [ 11 12 ].…”
Section: Introductionmentioning
confidence: 99%